Multifunctional Smart Bone Implants: Fiction or Future?—A New Perspective - Peres, Inês; Rolo, Pedro; Soares dos Santos, Marco P. (Frontiers in Bioengineering and Biotechnology, 2022)
Implantable medical devices have been developed to provide multifunctional ability to numerous bioapplications. In the scope of orthopaedics, four methodologies were already proposed to design implant technologies: non-instrumented passive implants, non-instrumented active implants, instrumented passive implants and instrumented active implants. Even though bone replacements are among the most performed surgeries worldwide, implant failure rates can still exceed 10%. Controversial positions multiply in the scientific community about the potential of each methodology to minimize the burden related to implant failures. In this perspective paper, we argue that the next technological revolution in the field of implantable bone devices will most likely emerge with instrumented active implants as multifunctional smart devices extracorporeally controlled by clinicians/surgeons. Moreover, we provide a new perspective about implant technology: the essence of instrumented implants is to enclose a hybrid architecture in which optimal implant performances require both smart instrumentation and smart coatings, although the implant controllability must be ensured by extracorporeal systems.